Factores psicológicos y fisiológicos asociados al rendimiento deportivo - Aplicaciones para su control y mejora en deportes de resistencia - - Ortigosa Márquez, Jesús Manuel (UMA Editorial, 2017)
Sports performance is a multidimensional concept, which both coaches and scientists try to split in order to develop strategies that optimize the athlete's performance in competition. Traditionally, research has been directed at studying the behavior of physiological parameters. However, a multidisciplinary research is needed to explain the interactions between the factors that compose it. In the disciplines of resistance (case of the doctoral thesis) it is necessary to consider the performance as an holistic concept, which requires the integration of the physiological and psychological aspects for its understanding. Thus, the objective of this thesis is, first, to identify the psychophysiological factors associated with sports performance. Second, to explore practical applications for evaluation and improvement. The first study aims to analyze the influence of RAE on national triathlon selection process (n = 1321) during the seasons 2013-2015. The results show higher performance among older female triathletes only in 100 m and 1000 m swimming timekeeping. These data agree with other findings in endurance (Costa et al., 2013), that observes how the athletes born in the last quartile of the year show a poor performance (Müller et al., 2015). This work has shown the importance of considering chronological age as part of the multifactorial performance concept, in addition to suggesting its consideration in selection procedures in sport.
Also, when it comes to identify the factors associated with sport performance in the endurance, it is not possible to ignore the cardiovascular capacity. Thus, the second study examines the heart rate variability (HRV), mainly due to its recent incorporation to research in the sport field. In order to apply this indicator, this work performs a wide review where it is defined the short duration intervals at rest (Al Haddad, Laursen, Chollet, Ahmaidi, and Buchheit, 2011) with a frequency of 3-4 times per week (Buchheit, 2014, Plews, Laursen, Kilding, and Buchheit, 2012) as the most appropriate method for the HRV evaluation. Also, this review has shown the statistical method in order to analyze the change (Hopkins, Hawley, and Burke, 1999) based on the weekly mean, compared to a baseline and its relation with psychological parameters as mood states (Sánchez, Romero, and Ortís, 2013) or sleep quality (Myllymäki et al., 2011). Therefore, this work shows the usefulness of resting heart rate variability to assess the body's response and improve performance in sport. The third research is a case study, which aims two objectives based in the previous results. The first, to evaluate the utility of the HRV to control the stress-recovery process in order to prevent non-functional over-reached states (NFOR). The second, to determine the relationships between HRV, training load and psychological parameters: sleep quality (SQ), mood state and social stress (SS. The Sheffé test showed differences in parasympathetic activity (Ln pNN50) when comparing the third period with the first one, detecting a significant reduction (p <0.05). The Welch test reveals, on the other hand, an increase in the Ln RHR in the last period compared to the second. This agrees with the low sleep quality scores in the last week, in addition to the subsequent results in the competition. Similarly, Pearson's test revealed a negative correlation (p <0.01) between the Ln RHR and sleep quality, and the total score on the mood state scale. This study evidences the utility of HRV as an indicator of the fitness level progression once its interpretation is together with RHR and psychological variables. In relation to the previous study, the fourth research aims to analyze the capacity of the HRV as a performance predictor and its relationship with the following psychological parameters: sleep quality, self-esteem and mood state. The Pearson test showed how the anxiety (POMS) correlated negatively with the natural logarithm of high frequency band (Ln HF) and positively with the natural logarithm of the very low frequency band (Ln VLF). However, no relationships were found for the variables self-esteem and sleep quality. On the other hand, the time in the time keeping was negatively associated with indicators of parasympathetic activity. These results suggest that HRV could be a valid performance indicator, and again, this parameter has been associated to psychological variables, in this case anxiety, in agreement with the results of other studies (César, Blásquez, Rhodes, and Ortís, 2009). Once the previous researches have pointed out some of the physiological and psychological factors involve in performance, also the objective of this doctoral thesis is analyzed strategies for enhancing sport performance, understood from an holistic approach. Therefore, the fifth study aims to examine the effect of regular practice of autogenic training (AT) on lung capacity, subjective vitality and competitive anxiety. The results show a significant increase (p <0.001) in subjective vitality and self-confidence post intervention (p <0.001). No differences were found in the physiological parameters. This research shows that the regular practice of AT may be useful to improve psychological parameters associated with athletic performance. Finally, while the previous study assesses an improvement strategy, the last work aims to satisfy the objective of creating practical applications for the optimization of sport performance. To this end, a web application has been designed that meets the scientific requirements, since each of its sections has a theoretical basis. The International Periodization Training Method (ITPM) provides a user-driven process for planning, designing, evaluating and controlling the training tasks. The trainer has form-state control tools based on the monitoring of physiological indicators such as HRV and psychological variables such as sleep quality or mood state, in accordance with the results of previous research in this thesis and indications of other authors (Al Haddad, Laursen, Chollet, Ahmaidi, and Buchheit, 2011, Buchheit, 2014, Plews et al., 2012). This effort places ITPM as the first app to plan and evaluate the stress-recovery process in sport science. This work, from the first research to the last, supposes an improvement of the understanding of the mechanisms that modulate the performance in competition, besides offering practical applications for its empowerment.
Keywords: Deportes - Aspectos psicológicos - Tesis doctorales; Variabilidad de la frecuencia cardiaca; Rendimiento; Psicología; Resistencia; Monitorización